Problematika Penerapan Pasal 28 Ayat (2) Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Yacob, Christovel Yamado (Legalita, 2024)
This study aims to identify Article 28 paragraph (2) of Law No. 19 of 2016 on the Amendment to Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) regulates the dissemination of information that potentially threatens freedom of expression. However, the application of this article has caused several problems that contradict the principle of legality, especially in the context of lex certa (a legal principle that requires the formulation of a crime to be clear). The phrase “causing hatred or hostility” in Section 28 Clause (2) of the ITE Law has a very broad and unspecific scope, allowing for different interpretations. This can lead to abuse and unfair prosecution of individuals who unintentionally spread information that is considered provocative. The provisions of Section 28 Clause (2) of the ITE Law do not have a further explanation of hatred, thus allowing for different understandings that lead to multiple interpretations in legal practice and in the context of Lex Certa, the application of Article 28 Paragraph (2) of the ITE Law must meet definite and clear legal requirements. The need for revision of Section 28 Clause (2) of the ITE Law to avoid multiple interpretations that have the potential for criminalization based on articles whose formulations are vague or unclear.